On the linkage between hydrology and society—learning from history about two-way interactions for sustainable development - Pande, S.; Uhlenbrook, Stefan (Springer, 2020)
The challenge of sustainable development is enshrined in the ambitious 2030 Agenda for Sustainable Development of the United Nations. The 17 goals and its various targets are unique with water being one of the cross cutting themes. Taking examples of past water dependent societies in a comparative setting, this paper challenges the new field of Archaeo-hydrology in how it could contribute to the 2030 Agenda based on what can be learned from past and contemporary water dependent societies. We find that societies have coped with climate variability by diversifying both in occupation, livelihoods and use of space. Sharing the costs of coordinating such diversification requires inclusive institutions and technological innovations. Similar to technology, new social institutions emerge in response to a changing environment. However, in tandem, slow out-migration of people seems to go on, driven by better livelihood opportunities outside. If technological innovation and institutional evolution are not rapid enough, then migration seems to take over as the adaptive mechanism in response to environmental changes resulting in rapid dispersal. This means that migration from smaller, less endowed societies can be expected to be rapid, with repetitive cycles of abandonment and rehabilitation after each critical climate or adverse environment events. Consequently, more place based local innovations should be encouraged and local economies should be diversified to increase the resilience so that vulnerable societies may inherit favourable know-how for a sustainable future under changing climatic conditions.